2019
DOI: 10.3390/ijms20081908
|View full text |Cite
|
Sign up to set email alerts
|

Goeckerman Therapy of Psoriasis: Genotoxicity, Dietary Micronutrients, Homocysteine, and MTHFR Gene Polymorphisms

Abstract: Goeckerman therapy (GT) of psoriasis vulgaris is based on the application of crude coal tar and ultraviolet radiation. We investigated DNA damage by the number of micronucleated binucleated cells (MNBC) in lymphocytes, serum homocysteine, vitamin B12, folic acid, and two polymorphisms (C677T and A1298C) in the MTHFR gene in 35 patients with exacerbated psoriasis vulgaris classified according to the psoriasis area and severity index (PASI) score and treated by GT. The median of PASI score decreased from ninetee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The uncertainty of interpretation is also supported by the absence of information about nutritional factors, especially levels of vitamin B 12 and folate, which may affect DNA synthesis and repair, and hence the levels of aberrated cells (Beranek et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The uncertainty of interpretation is also supported by the absence of information about nutritional factors, especially levels of vitamin B 12 and folate, which may affect DNA synthesis and repair, and hence the levels of aberrated cells (Beranek et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The results, however, are contradictory to the findings from other authors. For example, Asefi et al reported that the MTHFR 677 T allele was associated with an increased risk of psoriasis [ 50 ], whereas Beranek et al failed to find any association between the SNP and risk of psoriasis [ 45 ]. Two previous meta-analyses were conducted, and no significant association of the MTHFR 677 C/T with the etiology of psoriasis was found [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was found between Hcy and TNF-α, IFN-γ, IL-17α, IL-1β, TNF-α and IL-6 and increases the activity of matrix metalloproteinases, increases the activity of the nuclear transcription factor Nf-kB. Given these data, we can assume a positive correlation between homocysteine levels and psoriasis severity [36,38,39].…”
mentioning
confidence: 89%